Body mass index, lipid profile, and endothelial dysfunction gene polymorphism in women with early-onset and late-onset preeclampsia - Loskutova, Tetiana; Petulko, Albina; Donskaya, Yuliya (ScienceRise: Medical Science, 2024)
The aim: to investigate and analyze clinical parameters, laboratory biomarkers of lipid metabolism and endothelial dysfunction gene polymorphisms in early-onset and late-onset preeclampsia and to identify potential risk factor(s) for the development of early-onset preeclampsia. Materials and methods: a prospective case-control study included 133 women in the second half of pregnancy, including 46 with early-onset (EOP) and 87 with late-onset preeclampsia (LOP) and 34 conditionally healthy pregnant women with an uncomplicated obstetric history and no risk factors for preeclampsia. Concentrations of total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides in blood plasma were determined. Genetic polymorphisms of endothelial dysfunction (192 Q→R PON-1, 677 C→ T MTHFR) were studied using allele-specific polymerase chain reaction. Results: Early-onset preeclampsia is associated with an increased relative risk: preterm delivery by 2.08 times (95 % CI 1.48-2.93), operative delivery by 2.2 times (95 % CI 1.46-3.33), early operative delivery by 2.9 times (95 % CI 1.5-5.5), fetal distress during delivery by 3.78 times (95 % CI 1.2-11.9), a low score on the Apgar scale on the 1st minute, less than 6 points, by 2.59 times (95 % CI 1.84-3.66), on the 5th minute – 5.04 times (95 % CI 1.41-18.11), Grade III prematurity – 13.24 times (95 % CI 3.14-55.78) compared to women with late-onset preeclampsia. The study found that overweight was more often observed in patients with EOP (34.8 %) than in those with normal pregnancy (15.9 %) (p=0.02; OR=2.8; 95 % CI 1.03-7.7), obesity (BMI > 30 kg/m2) was more often recorded in those with LOP (33.33 %) than in the control group (3 (6.8 %)) (p=0.02; OR=6.8; 95 % CI 1.9-23.9). Patients in both groups with preeclampsia showed signs of dyslipidemia, but its significance in the development of early-onset or late-onset preeclampsia has not been separately proven. The study found that the number of carriers of MTHFR 677 TT in the group with EOP prevailed over the indicator of C group where there were no carriers of the pathological homozygote 677TT (p<0.05, OR= 20.73 95 % CI 1.16-371.28), and the T allele in the EOP group occurs 1.78 times more often than in the LOP group (p<0.05, OR=2.22; 95 % CI 1.26-3.88) and 2.43 times more often than in the C group (P<0.05, or= 3.15; 95 % CI 1.54-6.45). Conclusions: Factors of early onset of PE include pre-pregnancy, overweight, first pregnancy, a history of preeclampsia, and carrier of the 677T allele of the MTHFR gene